FAIR chemical structures in the Journal of Cheminformatics - Schymanski, Emma L.; Bolton, Evan E. (Journal of cheminformatics, 2021)
The ability to access chemical information openly is an essential part of many scientific disciplines. The Journal of Cheminformatics is leading the way for rigorous, open cheminformatics in many ways, but there remains room for improvement in primary areas. This letter discusses how both authors and the journal alike can help increase the FAIR ness (Findability, Accessibility, Interoperability, Reusability) of the chemical structural information in the journal. A proposed chemical structure template can serve as an interoperable Additional File format (already accessible ), made more findable by linking the DOI of this data file to the article DOI metadata, supporting further reuse .